Cyclobutane-1, 3-Diacid (CBDA): A Semi-Rigid Building Block Prepared by [2+2] Photocyclization for Polymeric Materials. Issue 1 (December 2017) - Wang, Zhihan; Miller, Benjamin; Mabin, Micah; Shahni, Rahul; Wang, Zijun; Ugrinov, Angel; Chu, Qianli
Abstract A previously overlooked building block, cyclobutane-1, 3-diacid (CBDA), is introduced to materials synthesis due to its great potentials. As an example of CBDA, α -truxillic acid or 2, 4-diphenylcyclobutane-1, 3-dicarboxylic acid, was readily synthesized from commercially availabletrans -cinnamic acid. This CBDA showed outstanding stability both in sunlight and upon heating. While its two carboxylic acid groups can be readily utilized in connecting with other molecules to form new materials, the cyclobutane ring was able to tolerate acid and base treatments showing good chemical stability. A series of cyclobutane-containing polymers (CBPs), namely poly-α -truxillates, were obtained by condensation betweenα -truxillic acid and diols including ethylene glycol, 1, 3-propanediol, 1, 4-butanediol, 1, 5-petanediol, and 1, 6-hexanediol. The structures of these poly-α -truxillates were analyzed by NMR, FT-IR, and HRMS. Powder X-ray diffraction results of the poly-α -truxillates indicated that they are semi-crystalline materials. Preliminary thermal, chemical, and photochemical tests showed that the poly-α -truxillates exhibited comparable stabilities to PET.